Western Influence in Contemporary Chinese Indonesian Weddings - Arya Sandy Damara Exelsior; Jenny Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2023)
In every culture, there is one important tradition: marriage. Marriage is important for Chinese Indonesians as it is considered to be a rite of passage. Due to globalization, many young Chinese Indonesians have little knowledge about Chinese traditions and tend to adopt Western wedding traditions as something more modern. Hence, Chinese Indonesian find new ways to convey their cultural identity as both Chinese and modern by using Chinese and Western wedding traditions. This article aims to identify the elements of Western culture that are commonly used in Chinese Indonesian weddings and the reasons they choose to use those elements. Western cultural elements commonly used in Chinese-Indonesian weddings can be seen in the wedding rituals, attire, and decorations. This article suggests that Chinese Indonesians who uses Western and Chinese wedding traditions create a new cultural identity as modern Chinese Indonesian. A hybrid culture emerges to form a contemporary or modern Chinese Indonesian wedding.